Analytical Hierarchy Process to Evaluate Supplier Performance in Timber Industry - Shelvy Kurniawan; Bayu Septian Nugraha; Prima Yolanda (Binus Business Review, 2018)
This descriptive and cross - sectional research was conducted to determine the priority criteria in supplier selection and the best supplier for Timber Industry as the unit of analysis. Data were collected through interview and questionnaire with the operational Manager of the company. The analysis method used was Analytical Hierarchy Process (AHP) that could assist decision making with criteria, sub-criteria, and several alternatives that had been determined by the company. The researchers find that there are four criteria which become the consideration in selecting supplier those are price, product, service, and delivery. From the analysis, it is foundthat the company should prioritize price compared to other criteria in selecting the supplier. Meanwhile, the other criteria (product, delivery, and service) sequentially become the second, third, and fourth priority criteria in selecting the suppliers. The other result of this research is the company can find the order of the best suppliers which can be recommended to the company.